Contaminants in the Urban Environment: Pharmaceuticals and Personal Care Products (PPCPs)—Part 2 - Yun-Ya Yang; Gurpal S. Toor (EDIS)
Pharmaceuticals and personal care products contain a variety of chemical substances that enter household wastewater from bath and shower, sinks, and washers and ultimately find their way into the environment. Continuous discharge of wastewater contributes to the accumulation of these substances in the environment — where they can be harmful to organisms. This publication is part of a series titled Contaminants in the Urban Environment. This series is intended to give state and local government officials, soil scientists, consulting engineers, extension agents, and citizens (1) a basic understanding of the occurrence, toxic effects, and source of various contaminants in the environment and (2) guidance on ways to protect human and environmental health. This 9-page fact sheet discusses the sources and impacts of PPCPs and offers common-sense ways we can protect our environment from PPCPs. Written by Yun-Ya Yang and Gurpal S. Toor, and published by the UF Department of Soil and Water Science, March 2015.